2019
DOI: 10.3390/nu11040908
|View full text |Cite
|
Sign up to set email alerts
|

Identification of N-Acetyl-S-(3-Cyano-2-(Methylsulfanyl)Propyl-Cysteine as a Major Human Urine Metabolite from the Epithionitrile 1-Cyano-2,3-Epithiopropane, the Main Glucosinolate Hydrolysis Product from Cabbage

Abstract: Brassica vegetables such as cabbage or pak choi contain alkenyl glucosinolates which can release epithionitriles and to a lesser degree isothiocyanates upon enzymatic hydrolysis. Here, for the first time, the metabolism of an epithionitrile was investigated in humans, namely 1-cyano-2,3-epithiopropane (CETP). After consumption of Brassica oleracea var. capitata f. alba and Brassica carinata sprouts, the main urinary metabolite of CETP was identified as N-acetyl-S-(3-cyano-2-(methylsulfanyl)propyl-cysteine usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
(49 reference statements)
0
8
1
Order By: Relevance
“…Occurrence and activity of the epithiospecifier protein (ESP) leads to the generation of ETNs from alkenyl-GLS aglucons as well as nitriles from non-alkenyl-GLS-aglucons (Burow et al, 2006;Matusheski et al, 2006). Many Brassica species release nitriles and ETNs upon GLS hydrolysis, among them B. oleracea and also B. campestris, B. carinata, and B. rapa (Macleod and Rossiter, 1985;Matusheski et al, 2004;Hanschen and Schreiner, 2017;Klopsch et al, 2017;Klopsch et al, 2018;Hanschen et al, 2019). So far, ESPs were characterized in A. thaliana (Lambrix et al, 2001;De Torres Zabala et al, 2005;Hanschen et al, 2018b) and in Brassica species, such as broccoli (B. oleracea var.…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence and activity of the epithiospecifier protein (ESP) leads to the generation of ETNs from alkenyl-GLS aglucons as well as nitriles from non-alkenyl-GLS-aglucons (Burow et al, 2006;Matusheski et al, 2006). Many Brassica species release nitriles and ETNs upon GLS hydrolysis, among them B. oleracea and also B. campestris, B. carinata, and B. rapa (Macleod and Rossiter, 1985;Matusheski et al, 2004;Hanschen and Schreiner, 2017;Klopsch et al, 2017;Klopsch et al, 2018;Hanschen et al, 2019). So far, ESPs were characterized in A. thaliana (Lambrix et al, 2001;De Torres Zabala et al, 2005;Hanschen et al, 2018b) and in Brassica species, such as broccoli (B. oleracea var.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, the reported range of Me‐CETP‐ N ‐Ac‐Cys concentrations was 24−37 µmol L ‐1 in urine samples, 180 min after sprout consumption with a 1.26‐fold higher dose of CETP given compared to the present study. [ 15 ] Here, concentration of five spot urines in the range of 160−190 min varied from 2.7 to 19 µmol L −1 (average 8.0 ± 6.5 µmol L −1 ), therefore being in a similar range but lower. This might be caused by a different drinking behavior as many of the participants in the present study drank frequently resulting in many spot urine samples and those had lower concentrations compared to participants with few urine donations (compare Figure S2, Supporting Information).…”
Section: Discussionmentioning
confidence: 87%
“…Recently, Me‐CETP‐ N ‐Ac‐Cys was identified as a human CETP metabolite in urine samples. [ 15 ] In the present study we investigated the bioavailability and metabolism of the ETNs CETP, CETB, and CETPent in a human intervention study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations